Karakteristik, Pengetahuan Gizi Ibu dan Status Gizi Balita (BB/TB) Usia 6-59 bulan - Aisyah Nanda Amirah; Mahmud Aditya Rifqi (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2019)
Background: Wasting is one of the nutritional problems that occur in toddlers. Wasting can inhibit the toddler’s growth and effected to their productivity in the future. Mothers have a significant role to affect the nutritional status of their child. The characteristics and nutrition knowledge of mother have a necessary influence in optimizing the nutritional status of the child. Objective: This study aimed to analyze the association of maternal characteristics and nutrition knowledge with nutritional status (WHZ) among 6-59 months of toddlerMethods: This study was an observational study with a cross-sectional study design. The study was conducted in October 2018 in Kesamben Village, Ngoro Sub District, Jombang. The research sample was 91 toddlers aged 6-59 months. The sample selection was done by random sampling technique. The independent variables were maternal characteristics (employement status and education) and nutrition knowledge of mother. The dependent variable was the nutritional status of toddler with anthropometric index weight for height (WHZ). The statistical test used were chi square and spearman test.Results: The results of the study showed a significant relationship between maternal employment and nutritional status (WHZ) of children aged 6-59 months (p = 0.001) while maternal education (p = 0.080) and mother’s nutrition knowledge (p = 0.593) were not relatedConclusion: Nutritional status of toddler is influenced by maternal employment. Unemployed mother can spend more time to control the diary intake of their child and improve their optimal nutritional status.ABSTRAK Latar Belakang: Wasting adalah salah satu permasalahan gizi yang terjadi pada balita. Wasting dapat mengakibatkan terhambatnya pertumbuhan balita serta mempengaruhi produktivitasnya kelak. Ibu berperan besar dalam mempengaruhi pemenuhan kebutuhan asupan anak. Karakteristik serta pengetahuan gizi ibu mempunyai peranan dalam mencapai status gizi yang sesuai untuk anak.Tujuan: Menganalis hubungan karakteristik ibu (pendidikan dan pekerjaan) dan pengetahuan gizi ibu dengan status gizi (BB/TB) dari balita usia 6-59 bulanMetode: Jenis penelitian ini merupakan penelitian observasional dengan rancangan desain cross-sectional. Penelitian dilselenggarakan pada bulan Oktober 2018 di wilayah kerja dari Puskesmas Kesamben Ngoro Kabupaten Jombang, Jawa Timur. Sampel penelitian yaitu 91 balita usia 6-59 bulan. Pemilihan sampel dilakukan dengan teknik random sampling. Variabel independen adalah karakteristik ibu (pendidikan dan pekerjaan) dan pengetahuan gizi ibu. Variabel dependen yang diteliti adalah status gizi balita dengan indeks antropometri berat badan menurut tinggi badan (BB/TB). Uji statistik yang digunakan yaitu chi square dan uji spearman.Hasil: Hasil penelitian menunjukkan adanya hubungan yang signifikan antara pekerjaan ibu dan status gizi anak usia 6-59 bulan (p = 0,001) sedangkan pendidikan ibu (p = 0,080) dan pengetahuan gizi ibu (p = 0,593) tidak berhubunganKesimpulan: Status gizi balita (BB/TB) berhubungan terhadap pekerjaan ibu. Ibu yang tidak bekerja dapat meluangkan lebih banyak waktunya untuk mengontrol asupan makanan anak dan dapat berdampak pada status gizi anak yang optimal.